CD11c+ dendritic cells mediate antigen-specific suppression in extracorporeal photopheresis. (8th November 2020) - Hackstein, H; Kalina, A; Dorn, B; Keil, I S; Baal, N; Michel, G; Brendel, C; Neubauer, A; Jakob, T; Bein, G
Summary: Extracorporeal photopheresis (ECP) represents one of the most widespread and effective cell therapies for graft- versus -host disease and other T cell-mediated disorders. However, the key factors affecting the therapeutic efficacy of ECP remain unclear. We hypothesized that therapeutic effects are mediated by ECP-treated antigen-presenting dendritic cells (DC). To test this hypothesis, we used the experimental model of contact hypersensitivity (CHS). The ECP's therapeutic activity improved when the total cell dose of the ECP-treated cells was increased. We used different haptens during sensitization to demonstrate that the anti-inflammatory activity of ECP is antigen-specific. This confirmed the hypothesis that professional antigen-presenting cells are involved in the mode of action. Also, the ECP's therapeutic activity was abrogated by the depletion of CD11c + DC, which represents fewer than 1% of all the ECP-exposed cells. Finally, we confirm the critical importance of CD11c + DC for ECP activity by showing that only a few purified CD11c + DC are sufficient to mediate its therapeutic effect. The finding that ECP-treated, physiological antigen-presenting DC alone mediate antigen-specific modulation of a pathological immune response may result in better-targeted interventions when treating patients. Graphical Abstract: